Potential Investigation of B3 Waste (Used Oil) of Motorcycle as Alternative Diesel Fuel - Yohanes Yohanes; Artinah Rukmana (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2020)
The waste or used engine oil is categorized as a Hazardous and Toxic Wastes (bahan berbahaya dan beracun/B3). However, it may have a great potential such as the alternative fuel. This study is proposed to investigate the potential of waste/used oils of motorcycle for diesel fuel. This research used Strengths, Weaknesses, Opportunities and Threats (SWOT) analysis and Quality Function Deployment (QFD) methods to investigate the potential of the used oils of motorcycle. From analysis result based the SWOT and QFD this was revealed the waste or used oil of motorcycle having an opportunity for alternative diesel engine fuel, which it has a positive impact both in economic and environmental terms. Based the test result of fuel consumption between diesel and waste or used oil in terms of costs obtained Rp. 2,532.00/KW for diesel fuel consumption and Rp.787.00/KW for waste or used oil. Therefore, the waste or used oil of motorcycle has potential become diesel fuel. However, it need further research to investigate the efficiency of the diesel engine performances.